THE SURVEY OF STUDENTS ATTITUDES TO VARIOUS KNOWLEDGE ASSESSMENT TOOLS FOR INSTRUCTION OPTIMIZATION - N. D. Bobrisheva-Pushkina; L. U. Kusnetsova; O. L. Popova; O. U. Sitnikova; V. V. Kozlov (Сеченовский вестник, 2016)
The study objective was to survey the medical students’ attitude to the objectivity and stressfulness of various forms of knowledge assessment, the level and causes of stress at the exams. 70.3% of the students consider the most objective an oral interview followed by a written exam, term paper (project or essay) presentation; structured test on ﬁ ll-in forms and computer testing were found least objective. The students think that main causes of stress at the exams were large amount and complexity of the exam materials, insuﬃcient coverage of the exam materials in the classroom and the changes in the exam timetable. The students consider exams in normal anatomy (38.7%) and pharmacology (35.3%) the most stressful. 70.5% of the students think that the return of the rating system will not increase the objectivity of knowledge assessment, 86.9% of studentsappreciated the exam in the cycle. The survey of the students' attitude to various forms of knowledge assessment gives information for instruction enhancement.